2017
DOI: 10.1016/j.mri.2017.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal MRI evaluation of neuroprotective effects of pharmacologically induced hypothermia in experimental ischemic stroke

Abstract: Pharmacologically induced hypothermia (PIH) shows promising neuroprotective effects after stroke insult. However, the dynamic evolution of stroke infarct during the hypothermic therapy has not been understood very well. In the present study, MRI was utilized to longitudinally characterize the infarct evolution in a mouse model of ischemic stroke treated by PIH using the neurotensin agonist HPI201. Adult male C57BL/6 mice underwent permanent occlusion of the right middle cerebra artery (MCA). Each animal receiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…cascade that is set in motion in the acute to subacute stages of ischemic injury, encompassing early BBB disruption and subsequent immune cell infiltration and propagation of inflammation. 23,24 In most stroke studies, BBB damage is typically measured 24 h after ischemia. 24 However, Shi et al 13 demonstrated early BBB disruption during the acute stage (<3 h) after stroke, followed by secondary irreversible BBB disruption.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…cascade that is set in motion in the acute to subacute stages of ischemic injury, encompassing early BBB disruption and subsequent immune cell infiltration and propagation of inflammation. 23,24 In most stroke studies, BBB damage is typically measured 24 h after ischemia. 24 However, Shi et al 13 demonstrated early BBB disruption during the acute stage (<3 h) after stroke, followed by secondary irreversible BBB disruption.…”
Section: Discussionmentioning
confidence: 99%
“…23,24 In most stroke studies, BBB damage is typically measured 24 h after ischemia. 24 However, Shi et al 13 demonstrated early BBB disruption during the acute stage (<3 h) after stroke, followed by secondary irreversible BBB disruption. As argued above, the acute stage of BBB disruption affects long-term outcomes by facilitating immune cell infiltration and subsequent neuroinflammatory processes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Early ischemic lesions are routinely evaluated on MRI-DWI in stroke medicine, and the size of the ischemic lesion has been shown to be associated with the degree of collateral circulation (Aoki et al, 2014;Campbell et al, 2013;Gawlitza et al, 2017;Kim et al, 2014;Lee et al, 2015;Verma et al, 2015), such that poor collateral circulation is closely related to the expansion of early ischemic lesions on MRI-DWI. In the experimental models, MRI has been used to evaluate lesion size and edema volume (Gupta, Sharma, Jagannathan, & Gupta, 2017;He et al, 2017;Huang et al, 2013;Okubo et al, 2007;Woo et al, 2017;Xu et al, 2015;Zhao et al, 2016) as in human stroke, and the beneficial effect of hypothermia on early ischemic lesions has been demonstrated in an MRI-DWI experiment (Wang et al, 2017). However, in experimental ischemia, the in vivo evaluation of leptomeningeal anastomoses throughout the entire hemisphere was technically challenging owing to small brain size; therefore, several groups, including ours, have applied the injection of latex beads (Todo et al, 2008) and contrast medium (Chen et al, 2007).…”
Section: Discussionmentioning
confidence: 99%